(untitled) (Bangladesh Journal of Animal Science, 2012)
The present study was designed to obtain existing baseline information on feeding and management practices of Red Chittagong (RC) cattle in two Upazilas of Chittagong district. The results showed that among 42 cattle owners, agriculture was the main occupation (52.38%). The percentage of RC cattle was about 70% and concentration was higher in Anowara than that of Chandanaish upazila. Farmers of the study area supplied on an average 4.93, 8.35, 2.25, 1.54 (kg/d) of rice straw, green grass, rice polish and wheat bran respectively. About 45.24%, 21.43%, 30.95% and 2.38% farmers supplied whole and dry straw, chopped and dry straw, chopped straw soaked with water and straw with green grass respectively. About 55%, 14.3% and 13% of the farmers followed stall feeding (cut and carry system), grazing and stall feeding with grazing respectively for feeding green grasses. The average daily grazing period of cattle was 7.25 hours with highest and lowest 9 and 5 hours respectively daily. About 26.19% of the respondents made cattle house using tin and chatai. 81% of the cattle house had sufficient ventilation and light. The major disease outbreak in the area was FMD, which was 45% of the total disease incidence. About 36% respondents used vaccine and 95% took help from village doctor for treatment of their cattle. Cattle rearing contributed more (about 57%) to income generation of low income group than medium (6.89%) and high (8.25%) income groups. 35% respondents showed their interest to grow fodder crops and 65% of farmers were reluctant to grow fodder crops due to limitation of crop land. http://dx.doi.org/10.3329/bjas.v41i1.11974